2016
DOI: 10.1259/bjr.20150250
|View full text |Cite
|
Sign up to set email alerts
|

The validity of investigating occult hip fractures using multidetector CT

Abstract: We recommend the use of MDCT as a safe and appropriate first-line investigation for NOF fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 18 publications
2
27
0
Order By: Relevance
“…Standard of care diagnosis of skeletal injuries relies on plain XR, although XR might miss a substantial portion of fractures of the rib cage and pelvic ring [10][11][12][13]. Evaluation of the vertebral column is frequently limited to imaging of the cervical spine [14], whereas supplementary imaging of the thoracolumbar spine often depends on clinical presentation and clinical experience of the treating physician, which might be submitted to diagnostic inaccuracy [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Standard of care diagnosis of skeletal injuries relies on plain XR, although XR might miss a substantial portion of fractures of the rib cage and pelvic ring [10][11][12][13]. Evaluation of the vertebral column is frequently limited to imaging of the cervical spine [14], whereas supplementary imaging of the thoracolumbar spine often depends on clinical presentation and clinical experience of the treating physician, which might be submitted to diagnostic inaccuracy [15].…”
Section: Discussionmentioning
confidence: 99%
“…Heikal et al found 58% of hip and pelvic ring fractures were missed in XR [11]. Thomas et al showed that from 199 negative XR of the pelvic ring, 55% of the fractures of the pelvic ring and the proximal femur were missed [13]. Another study with consecutive imaging of the pelvic ring yielded a LR − of 0.89 and 0.27 for detection of sacral fractures and pubic bone fractures, respectively [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been considerable investigation into the accuracy of noncontrast CT for detection of radiographically occult proximal femoral fractures, although these studies have been invariably retrospective in nature, have used inconsistent methodology, and at times produced conflicting results. In one study of 199 patients, CT was negative for fracture in 93 patients, and none were found to have undiscovered fractures at 4-month clinical follow-ups [34]. Another similar study with 68 patients found no missed fractures in 27 patients with negative CT scans, although it was not clear if clinical follow-up was as comprehensive [46].…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%
“…CT Pelvis and Hips. Although not as sensitive as MRI, noncontrast CT is also reserved as a problem-solving modality following radiography either to evaluate for radiographically occult fracture or to better depict fracture morphology for treatment planning purposes [34,35].…”
Section: Discussion Of Procedures By Variantmentioning
confidence: 99%